Teacher transformation achieved through participation in the National Writing Project’s invitational summer institute - Caswell, Roger L (Kansas State University, 2007)
Professional development of in-service teachers continues to increase, but not all programs are successful in promoting teacher learning and student improvement. This qualitative study offers an examination of how one professional development program, The National Writing Project, with its teachers-teaching-teachers model is making a difference. The National Writing Project is one of the longest running, most cost-efficient, and most successful professional development programs in education. The purpose of this study was to identify factors influencing teacher transformation. Five areas were addressed: (1) the identification of transformation factors; (2) the relationship of personal literacy as it affects professional change; (3) being a member of a learning community and how it affects personal learning; (4) being a member of a learning community and how it affects professional learning; and (5) the role of spirituality in transformation. The setting was the National Writing Project's Invitational Summer Institute as it examined how fellows, first time participants, perceived their learning. Participants were from 17 different writing project sites across the United States. Data collection involved three distinct sources: (1) selection of participant and rationale provided by site directors of writing project sites; (2) audio-taped long interviews of each participant; and, (3) a follow-up focus group conducted in an electronic discussion board. The findings highlighted an interweaving of five factors influencing teacher transformation: (1) identification and application of knowledge for self and students; (2) reflection of learning and practice; (3) collaboration; (4) active and on-going involvement; and, (5) supportive and safe environment. When these five transformative factors are designed and implemented in the professional development of teacher in-service, teachers are provided an opportunity to personally learn which leads to professional learning and improved instruction for student learning. Excerpts from each data collection, recommendations for future research, and appendices to replicate the study are provided.
Keywords: Transformation; Professional development; Teacher efficacy; Spirituality; National Writing Project; Education, Adult and Continuing (0516); Education, Curriculum and Instruction (0727); Education, Teacher Training (0530)